2013
DOI: 10.1016/j.gca.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of thallium isotope fractionation during adsorption to manganese oxides

Abstract: Lett. 197,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 48 publications
1
71
0
Order By: Relevance
“…Such an approach was not employed here because leaching has the potential to generate significant stable isotope effects for Tl (e.g., Nielsen et al. ). Hence, Pb isotope measurements were carried out for all samples and these data in combination with Pb‐Tl elemental ratios were employed to assess and, using model calculations, semiquantitatively determine the extent of terrestrial Pb contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach was not employed here because leaching has the potential to generate significant stable isotope effects for Tl (e.g., Nielsen et al. ). Hence, Pb isotope measurements were carried out for all samples and these data in combination with Pb‐Tl elemental ratios were employed to assess and, using model calculations, semiquantitatively determine the extent of terrestrial Pb contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Trivalent thallium (Tl 3+ ) can also exist on Earth under highly oxidising conditions (Bately and Florence , Vink ), for example in the structure of the ferromanganese (Fe–Mn) mineral hexagonal birnessite (Peacock and Moon , Nielsen et al . ).…”
Section: The Literature Mc‐icp‐ms Tl Isotope Ratio Data For Igneous Rmentioning
confidence: 97%
“…It has been observed that coordination changes of Mo, U, Tl, Cu and Zn during adsorption onto Mnoxyhydroxides led to resolvable isotopic fractionation (Barling et al, 2004;Brennecka et al, 2011b;Nielsen et al, 2013;Little et al, 2014). Generally, metal complexes with smaller coordination number and shorter bond length have stronger chemical bonds, favoring incorporation of heavier isotopes (Schauble et al, 2004).…”
Section: Change In U Speciation During Incorporation Into Cacomentioning
confidence: 99%
“…Although no resolvable U isotopic fractionation has been observed between modern aragonite and calcite samples and seawater (Weyer et al, 2008;Romaniello et al, 2013) (Juillot et al, 2008;Brennecka et al, 2011b;Wasylenki et al, 2011;Nielsen et al, 2013;Little et al, 2014;Bryan et al, 2015). Previous studies found that the predominant U(VI) species in seawater, UO 2 (CO 3 ) 3 4-, was directly incorporated as a unit into aragonite without coordination change or reduction (Reeder et al, 2000).…”
mentioning
confidence: 99%